Estimation of FMAX and ISB in microprocessors. - Abulafia, Y.
Inherent process device variations and fluctuations during manufacturing have a large impact on the microprocessor maximum clock frequency and total leakage power. These fluctuations have a statistical distribution that calls for usage of statistical methods for frequency and leakage analysis. This paper presents a simple technique for accurate estimation of product high-level (Full Chip) parameters such as the maximum frequency (FMAX) distribution and the total leakage (ISB). Moreover, this technique can grade critical paths by their failure probability and perform what-if analysis to estimate FMAX after fixing specific speed paths. Using our FMAX/ISB prediction, we show good correlation with silicon measurements from a production microprocessor.
Keywords: FMAX estimation; ISB estimation; Critical path analysis; Failure probability; Frequency analysis; Full chip parameters; High-level parameters; Leakage analysis; Maximum clock frequency; Maximum frequency distribution; Microprocessors; Total leakage power